Cenozoic deformation in the Tauern Window (Eastern Alps) constrained by in situ Th-Pb dating of fissure monazite - Ricchi, Emmanuelle; Bergemann, Christian A. (Solid earth, 2020)
Thorium-lead (Th-Pb) crystallization ages of hydrothermal monazites from the western, central and eastern Tauern Window provide new insights into Cenozoic tectonic evolution of the Tauern metamorphic dome. Growth domain crystallization ages range from 21.7 ± 0.4 to 10.0 ± 0.2 Ma. Three major periods of monazite growth are recorded between ∼ 22-20 (peak at 21 Ma), 19-15 (major peak at 17 Ma) and 14-10 Ma (major peak around 12 Ma), respectively, interpreted to be related to prevailing N-S shortening, in association with E-W extension, beginning strike-slip movements and reactivation of strike-slip faulting. Fissure monazite ages largely overlap with zircon and apatite fission track data. Besides tracking the thermal evolution of the Tauern dome, monazite dates reflect episodic tectonic movement along major shear zones that took place during the formation of the dome. Geochronological and structural data from the Pfitschtal area in the western Tauern Window show the existence of two cleft generations separated in time by 4 Ma and related to strike-slip to oblique-slip faulting. Moreover, these two phases overprint earlier phases of fissure formation. Highlights. In situ dating of hydrothermal monazite-(Ce). New constraints on the exhumation of the Tauern metamorphic dome. Distinct tectonic pulses recorded from east to west.
Gesehen am 29.04.2020